(untitled) (Research, Society and Development, 2021)
Introduction: Magnesium participates in energy metabolism, regulation of ion transporters, antioxidant defense and important metabolic aspects for performance in sports practice. Objective: This study aims to describe the benefits of magnesium and its main food sources, point out the damage to health resulting from the mineral deficiency and correlate the role of magnesium in people who exercise. Methods: This is an integrative literature review study, contributing to the process of systematization and analysis of results based on other independent studies on the topic discussed. Results: Magnesium is an antioxidant involved in more than 300 metabolic and bioenergetic reactions in the body, physical exercise is intended to lead to the redistribution of magnesium in the body during and after practice, varying according to the type of exercise, and the state of the individual, although it is a mineral contained in easily accessible foods, there is an inadequacy in its intake with its reduced consumption by the population. Final considerations: It is evident the importance of magnesium intake, since the mineral is directly linked to several processes that affect muscle function, however there is a great lack of studies on the subject.